Konsep Pendidikan Transformatif dalam Pengkajian Islam Berbasis Dekonstruksi Syariah ‘Abdullah Ahmed An-Naiem - Abd. Latif; Rahmatun Nair; Muhammad Rusydi (Jurusan Tarbiyah STAI Al-Gazali Bone, 2026)
This research article focuses on examining the concept of transformative education in the study of Islam based on sharia deconstruction 'Abdullah Ahmed an-Naiem. Through literature research conducted by examining various relevant literature, it was found that Islamic studies based on the deconstruction of sharia 'Abdullah Ahmed an-Naiem are loaded with transformative educational concepts that can be used as a paradigmatic framework in the future. By positioning sharia as an educational object that continues to move in response to very dynamic human life, the deconstruction of sharia 'Abdullah Ahmed an-Naiem can be a model for transformative educational development so that sharia becomes a forum for developing human potential in transformative thinking.